1983
DOI: 10.1159/000198913
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Immunoreactive Trypsin, Pancreatic Elastase and Chymotrypsin in Extracts of Human Feces and Ileostomy Drainage

Abstract: The total daily amount of extractable cationic trypsin, chymotrypsin, and pancreatic elastase 2 in feces and ileostomy fluids has been studied in normal individuals and healthy colectomized subjects. Quantitation was performed using immunological assays with polyethylene glycol as a fecal marker. The extractable amount of each of these enzymes in the feces of normal individuals was less than 1 mg/24 h. However, in fecal extracts from antibiotic-treated normal individuals a 100-fold increase in immunoreactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Furthermore, studies on the possi ble absorption o f 1311-labelled albumin in the rat have shown the recovered radioactivity in serum to be free iodine in accordance with our results [19], Neither pancreatic extract, extracts from rat intestinal mucosa nor gas tric juice could deiodinate the labelled pro tein. A prerequisite for studies such as these is the effective blocking of the I-binding sites in the organism by giving nonlabelled Nal before the study [20], Using immunochemical methods we found earlier about 10% of the total daily pancreatic production of cationic trypsin in ileostomy contents and about 0.1 % in fecal extracts [6]. These figures roughly correspond to the recovery of nondialyzable extractable radioactive substances in the supernatants mentioned above.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, studies on the possi ble absorption o f 1311-labelled albumin in the rat have shown the recovered radioactivity in serum to be free iodine in accordance with our results [19], Neither pancreatic extract, extracts from rat intestinal mucosa nor gas tric juice could deiodinate the labelled pro tein. A prerequisite for studies such as these is the effective blocking of the I-binding sites in the organism by giving nonlabelled Nal before the study [20], Using immunochemical methods we found earlier about 10% of the total daily pancreatic production of cationic trypsin in ileostomy contents and about 0.1 % in fecal extracts [6]. These figures roughly correspond to the recovery of nondialyzable extractable radioactive substances in the supernatants mentioned above.…”
Section: Discussionmentioning
confidence: 81%
“…It has been demonstrated that most of the pancreatic enzymes are de graded in the small intestine [5][6][7], Alterna tive metabolic pathways for the pancreatic endopeptidases have been discussed, such as enteropancreatic circulation [8][9][10], in activation by the intestinal microflora [6,11] or binding to intestinal particles [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal contents are strongly proteolytic and although much of this activity is undoubtedly pancreatic in origin (Bohe et al, 1983), recent evidence has indicated that colonic bacteria, particularly Bacteroides spp., may contribute substantially to protein breakdown (Macfarlane et al, 1985. At present, however, little is known concerning the factors that control bacterial proteolysis in the large gut, or of the significance of this process in the microbial ecology of the colon.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the three rumA copies can be transcribed as an operon also containing the downstream genes rumM, rumT, and rumX. However, our results demonstrate that most transcripts initiated at the rumA promoter terminate at the junction between rumA 3 and rumM, likely at the stem-loop structure named t 3 . The stem-loops located downstream of the structural gene are conserved in many lantibiotic gene clusters and are considered to function as transcriptional attenuators or as sites protecting the structural-gene mRNA against exonuclease degradation (34,41).…”
Section: Discussionmentioning
confidence: 62%
“…However, enzymatic activities measured in the terminal part of intestinal tract, which harbors most of the microbiota, can be highly variable. Pancreatic enzymes undergo a progressive inactivation by both host and bacterial factors during their passage through the entire intestine (3,19,37). The concentration of trypsin required for the in vivo production of an antimicrobial substance by R. gnavus E1 appears to be much lower than that supplied by pancreas (36), but the impact of other proteolytic activities remains to be elucidated under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%